QUALITY AND COMPETITIVENESS OF THE PRODUCTION IS THE BASIS FOR THE STABLE POSITION IN THE MARKET - N. A. Kabernik (Литьë и металлургия)
At present time the works has available 22 certificates of conformity on the production.Audits on the certificates of conformity according to the new standards version are regularly carried out. The government of the works has determined the strategy on the increase of competitiveness of the production, based on its high quality and effective operation of the quality management system, fixed in the basic document — Politics of RUP ''BMZ’' in the field of quality''.